Radiation-Induced Cardiovascular Disease: Mechanisms and Importance of Linear Energy Transfer - Sylvester, Christopher B.; Abe, Jun-ichi; Patel, Zarana S.; Grande-Allen, K. Jane (Frontiers in Cardiovascular Medicine, 2018)
Radiation therapy in the form of photons and protons is a well-established treatment for cancer. More recently, heavy charged particles have been used to treat radioresistant and high-risk cancers. Radiation treatment is known to cause cardiovascular disease which can occur acutely during treatment or years afterward in the form of accelerated atherosclerosis. Radiation-induced cardiovascular disease (RICVD) can be a limiting factor in treatment as well as a cause of morbidity and mortality in successfully treated patients. Inflammation plays a key role in both acute and chronic RICVD, but the underling pathophysiology is complex, involving DNA damage, reactive oxygen species, and chronic inflammation. While understanding of the molecular mechanisms of RICVD has increased, the growing number of patients receiving radiation therapy warrants further research to identify individuals at risk, plans for prevention, and targets for the treatment of RICVD. Research on RICVD is also relevant to the National Aeronautics and Space Administration (NASA) due to the prevalent space radiation environment encountered by astronauts. NASA’s current research on RICVD can both contribute to and benefit from concurrent work with cell and animal studies informing radiotoxicities resulting from cancer therapy. This review summarizes the types of radiation currently in clinical use, models of RICVD, current knowledge of the mechanisms by which they cause cardiovascular disease, and how this knowledge might apply to those exposed to various types of radiation.